2014
DOI: 10.1177/0886260514533154
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth in Survivors of Intimate Partner Violence

Abstract: Adverse consequences of intimate partner violence (IPV) are well documented, whereas less research has explored positive changes. Recent efforts indicate that survivors report posttraumatic growth (PTG), but the schema reconstruction hypothesis by which this is achieved is in need of further investigation. One model of PTG suggests that growth is triggered by trauma(s) that challenges an individual's assumptive world. This threat promotes cognitive processing and schema reconstruction that fosters a sense of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…While reviewing overall quantitative studies looking at outcomes of PTG and how it relates to IPV within heterosexual relationships, the limited results are variable. Valdez and Lilly [ 52 ] found in their study of PTG in female (heterosexual) survivors of IPV, and similar to earlier research conducted by Calhoun and Tedeschi [ 53 ], that 87% of their respondents reported PTG post-IPV related trauma found that women who experienced more abuse in their relationships experienced higher rates of posttraumatic growth. Doane [ 54 ] explored the role of timeline posttrauma and found that the greater the distance the participant had from the abusive relationship, the higher the scores on the PTGI, but this study looked at IPV survivors in comparison to violent crime survivors and did not focus on sexual minorities.…”
Section: Posttraumatic Growthsupporting
confidence: 71%
See 2 more Smart Citations
“…While reviewing overall quantitative studies looking at outcomes of PTG and how it relates to IPV within heterosexual relationships, the limited results are variable. Valdez and Lilly [ 52 ] found in their study of PTG in female (heterosexual) survivors of IPV, and similar to earlier research conducted by Calhoun and Tedeschi [ 53 ], that 87% of their respondents reported PTG post-IPV related trauma found that women who experienced more abuse in their relationships experienced higher rates of posttraumatic growth. Doane [ 54 ] explored the role of timeline posttrauma and found that the greater the distance the participant had from the abusive relationship, the higher the scores on the PTGI, but this study looked at IPV survivors in comparison to violent crime survivors and did not focus on sexual minorities.…”
Section: Posttraumatic Growthsupporting
confidence: 71%
“…By understanding the intersection of minority stress, intimate partner violence and the possibility of posttraumatic growth, stronger programs in emergency shelters and in inpatient and outpatient counseling programs could be developed and implemented that are tailored to the nuanced needs of SMW. Deeper understanding of how individuals and marginalized groups can adapt positively from experienced trauma answers Valdez & Lilly’s recent [ 52 ] call for a more comprehensive framework for working with trauma survivors. Through a clearer understanding of this posttrauma adaptation, more nuanced programming that fosters these domains may prevent future behavioral health risk factors for survivors and increase the ability to not only survive, but thrive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A person's cognitive processes play a role in post-traumatic growth. The traumatic events people experience lead to a change in existing schema (Valdez & Lilly, 2015;Tedeschi & Calhoun, 1995;. When a person accepts the reality of an experienced event, acceptance comes to fruition (Tedeschi & Calhoun, 1995).…”
Section: Similarly M45 Expressedmentioning
confidence: 99%
“…This is difficult because we do not know in advance who will experience a trauma. One small study attempted to address this issue by comparing changes in assumptions among survivors of physical intimate partner violence who had or had not experienced interpersonal revictimization 1 year later (Valdez & Lilly, 2015). If traumatic events shatter assumptions, those who were revictimized should report more negative changes in assumptions than those who were not revictimized.…”
Section: Violations Of Global Meaningmentioning
confidence: 99%